Mathematical Modelling Of Unsteady Nanofluid Flow For Heat, Mass And Microorganism Transfers With Magnetic And Slip Effects - Latiff, Nur Amalina Abdul (2018)
The study of flow problems related to the magnetic field, nanofluid, and microorganism are important especially in microfluidic devices. The advantages of microfluidic devices are its small size, low cost, and low consumption, especially for biological studies. The microorganisms in the nanofluid are essential to prevent nanoparticle agglomeration, to improve the stability of the nanofluids, to enhance mixing and hence enhance mass transfer in microfluidic devices. This thesis investigates the modified mathematical models to study the boundary layer flow for heat, nanoparticle mass, and microorganism transfers in the biochemical process involving microfluidic devices. Specific nanofluid flow problems under various geometries such as flow over stretchable/shrinkable rotating disk, flow between two parallel disks, flow over a vertical rotating cone, and micropolar nanofluid flow over a stretching/shrinking sheet were investigated. The effects of magnetic, Stefan blowing, and various slips (velocity slip, thermal slip, nanoparticle mass slip, and microorganism slip) were incorporated into the models. Both the Newtonian and non- Newtonian (micropolar) nanofluids have been taken into account. Appropriate transformations have been used to transform the partial differential equations into nonlinear ordinary differential equations. The differential equations have been solved numerically using the finite difference method coupled with the Richardson extrapolation technique in Maple software